Pengelolaan Sampah Rumah Tangga di Wilayah Kerja Puskesmas - Amalia, Riski; Sari Murni, Nani; Arie wahyudi; Yusnilasari (Avicenna: Jurnal Ilmiah, 2024)
Background: Everyone produces waste every day. Various human activities, both directly and indirectly, produce waste. The more sophisticated technology in the world, the more waste will be generated. Environmental cleanliness, including the presence of rubbish, has a big impact on everyone's health. Based on a field survey conducted by the author in the Celikah Community Health Center working area, OKI Regency, the absence of a Temporary Waste Disposal Site (TPSS) is the main cause of community behavior in managing household waste. Method: This type of quantitative research uses descriptive analytical techniques with a cross-sectional design. The research was carried out in the working area of the Celikah Community Health Center, Ogan Komering Ilir Regency in February-April 2024. The population in this study were all heads of families (KK) in the working area of the Celikah District Health Center. OKI with a total sample of 99 people taken using Purposive Sampling Technique. Data analysis was carried out univariately, bivariately using the Chi-Square Test. Results: The research results showed that knowledge had a value of p = 0.000, attitude p = 0.000, education p = 0.000, social economy p = 0.000 and availability of facilities p = 0.000 Conclusion: There is a relationship between knowledge, attitudes, education, socio-economic level and availability of facilities and household waste management in the Puskesmas work area. Keywords: Management, Waste, Household, Community Health Center